PERBANDINGAN PENGARUH MODEL PEMBELAJARAN TIME TOKEN DENGAN THINK TALK WRITE TERHADAP KETERAMPILAN SOSIAL PESERTA DIDIK DALAM PEMBELAJARAN IPS DI SMPN 10 PALEMBANG - Hamidah; Yulia Djahir; Siti Fatimah (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2017)
This study discusses the comparative influence learning models of learning Time Token with Think Talk Write to the social skills of students in learning social studies in junior high school N 10 Palembang. The formulation of the research problem, namely